2017
DOI: 10.1002/pd.5180
|View full text |Cite
|
Sign up to set email alerts
|

The use of fetal neurosonography and brain MRI in cases of cytomegalovirus infection during pregnancy: A retrospective analysis with outcome correlation

Abstract: Adding MRI in CMV-infected cases with a normal neurosonographic follow-up should be weighed against a nonnegligible rate of false positive and inconclusive findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 29 publications
5
46
0
Order By: Relevance
“…From the existing literature, it is quite clear that CMV affected fetuses and newborns with signs of CNS involvement are at an increased risk of presenting with CMV related symptomatology. On the other hand, our group and others have shown that the absence of signs of CNS involvement during fetal life or after birth in the presence of CMV infection are almost invariably associated with a normal developmental outcome, with a residual risk of hearing deficits of approximately 5%. The objective of the present study was to assess the significance of different subtle CNS imaging findings considered to be associated with CMV but for which the prognosis is still controversial.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…From the existing literature, it is quite clear that CMV affected fetuses and newborns with signs of CNS involvement are at an increased risk of presenting with CMV related symptomatology. On the other hand, our group and others have shown that the absence of signs of CNS involvement during fetal life or after birth in the presence of CMV infection are almost invariably associated with a normal developmental outcome, with a residual risk of hearing deficits of approximately 5%. The objective of the present study was to assess the significance of different subtle CNS imaging findings considered to be associated with CMV but for which the prognosis is still controversial.…”
Section: Discussionmentioning
confidence: 85%
“…In our previous study, we found five infected fetuses with isolated LSV on US and normal MRI. All these newborns were asymptomatic and developing normally . Benoist et al found normal development in eight infected newborns with isolated LSV on brain US .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…As mentioned in other sections, fetal MRI is expanding its diagnostic role, particularly in the brain. This includes assessment of brain effects from anomalies in other organs, such as the heart, and of congenital infections …”
Section: Diagnosis Of Fetal Brain Anomalies By Mrimentioning
confidence: 99%